Boards of Directors and Corporate Governance Outcomes: A Literature Review - Albergarias Lopes , Raphael de Oliveira; de Oliveira Dias, Murillo (Advances in Social Sciences Research Journal, 2026)
Using an extensive database of n=117 references, this volume explores the relationship between the composition of a company’s board of directors and observed outcomes of its governance. The papers are organized around six central themes: (a) board diversity, (b) board independence, (c) board size and structure, (d) board capital and resource dependence, (e) boards and innovation, and (f) boards and CSR. The themes together reflect the multiple roles that boards are meant to play in enhancing legitimacy and stakeholder trust, creating, monitoring, enforcing accountability, achieving efficiency and representation, accessing capital and other resources, and sustaining long-term value. Our discussion of the paper brought together these issues. We used the paper to explore our seminar research questions. In particular, we explored the paper's argument that a board's effectiveness depends on a combination of characteristics and their interactions. We also explored the paper's broader argument that the model of the board as merely a monitoring body is insufficient and that the board's design is a key strategic tool for building resilience, gaining legitimacy, and delivering sustained value in the longer term.